Variability in condensation water and its determinants in arid regions of north‐western China - Fang, Jing (Ecohydrology, 2020)
Condensation water plays an important ecohydrological role in arid and semi‐arid regions. However, little is known about the factors determining the formation of condensation over long term, especially in desert oases in arid areas. During 2005–2014, we investigated the main limiting factors in formation of condensation water for five different surfaces (interdune, dune top, flat vegetation‐free sand, artificial grassland and plantation forest), sand particle sizes, and temperature and humidity control experiment in a typical arid region of north‐western China. Results showed that changes in microhabitat resulting from different surface conditions had a significant influence on the amount of condensation water in arid desert ecosystem. Except for sand particle sizes 0.2–0.02 and 2–0.2 mm, the amount of average daily condensation for different sand particle sizes differed significantly (P < 0.05) and decreased with an increase in sand particle size. Air temperature (AT), relative humidity (RH), air and surface temperature range (RT) and wind speed (WS) can significantly (P < 0.05) affect the formation of condensation water in arid regions, and the thresholds of condensation water formation were RH > 25% and WS < 3.50 m s−1. Such effects, however, differed among the different surfaces due to different conditions of soil characteristics, microhabitats and regional climate. These results suggest that the influence of site characteristics, microhabitats and regional climate on the formation of condensation water should attract more attention and that both the relative importance and the interactions among different determining factors will contribute to a better understanding of the mechanistic determinants for the formation of condensation water in arid areas.